Praktik Pengobatan Ruqyah di Hamdalah dan Majelis Dzikir Ar-Rahman Kota Makassar: Tinjauan Hukum Islam - Irwan, Nursafitri; Idrus, Achmad Musyahid; Akmal, Andi Muhammad (Universitas Islam Negeri Alauddin Makassar, 2023)
This article discusses the review of Islamic Law on the Practice of Ruqyah Medicine in Hamdalah and the Ar-Rahman Dhikr Council of Makassar City. By using qualitative descriptive research types. Field research (Field Research) this type of research is that researchers go directly to the field to make direct observations related to a phenomenon that occurs. The results of this study show that the implementation of ruqyah treatment in the hamdalah and dzkiri ar-rahman assembly of the place by reciting Qur'anic verses and prayers that have been applied in accordance with the teachings of the Prophet that allow without violating the sharia law of Islam. Treatment of ruqyah by performing yasinan, dhikr together and performing ruqyah stages in accordance with the teachings of Islamic law. The analysis of the Islamic legal view of the practice of ruqyah medicine is that although ruqyah was initially forbidden and now the law is permissible because ruqyah therapy is tajribah (experimental) then its legal status can change which originally the prohibition can change to sunnah according to the ijtihad of the scholars, as long as the therapy is within the limits of shari'i then it is permissible.